Advertisement Remove all ads

Solve for X : 25x-1 = 4 23x + 1 - Mathematics

Sum

Solve for x : 25x-1 = 4 23x + 1

Advertisement Remove all ads

Solution

 25x-1 = 4  x 23x + 1
⇒  25x-1 = 2x 23x + 1
⇒  25x-1 = 22 + 3x + 1
⇒  25x-1 = 23x + 3
We know that if bases are equal, the powers are equal
⇒ 5x - 1 = 3x + 3
⇒ 5x - 3x = 3 + 1
⇒ 2x = 4
⇒ x = `4/2`
⇒ x = 2.

Concept: Solving Exponential Equations
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 9 ICSE
Chapter 7 Indices (Exponents)
Exercise 7 (B) | Q 1.2 | Page 100
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×